Characterisation and implementation of high‐order backscatter modulation for IoT applications. Issue 15 (5th November 2019) - Jordão, Marina; Correia, Ricardo; Carvalho, Nuno Borges
Abstract : The backscatter modulation has been used as an emerging technology in the Internet of Things (IoT), due to the hardware simplicity and low power consumption. Moreover, this technology is being combined with wireless power transfer scenarios in order to overcome a large number of batteries used. With recent development of backscatter systems for high bit‐rate communications, the design of a calibrated measurement system to characterise and calculate the optimum performance for M‐ary quadrature amplitude modulations, emerge as a requirement in IoT measurements. The main objective of this work is to characterise a backscatter modulation system, considering two characterisation approaches, a cable test measurement, and an Over‐The‐Air measurement. Thus, the characterisation of high‐order backscatter modulators can be executed to anticipate its performance in real scenarios. In this work, a dual‐band high‐order backscatter modulator will be presented and characterised for different modulations in free‐space, and the Error Vector Magnitude results will be computed.